(3OQ GdfUGFMs - (3GdNGOej GdQhej GdMfaj, YHO Gddg Hf eMeO Hf eUWai, (B1192 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfYe hChdi (B...(3hEf cJGH TjNfG hhGdOfG GdEeGe GdMeO ddg CQOa GdJSejI HGdJMejO dchf GdMeO aj GHJOGA cd Pj TCf CeQG YXjeG Hg jMUd GdGbJOGA HGdbQBf GdYXje hGdGeJKGd (B...s
(3BNQgG (B:s
(3aEf CfaS GdhUGjG LeY faS HeYfi GdYjf hGdPGJ (B, (3CfaS GdYWGjG GSe JaVjd hGdChd HVe GdaGA hGdKGfj HaJMgG hajg JLfjS fajS hjMJed Gf jchf GdKGfj cGdChd hGdeYfi aEf PhGJ GdhUGjG JeJs
(3JGQjN GdJCdja(B: 1179 : 1181 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\292s
(3eYLe GdeDdajf (B2\292s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs